PENGARUH DUKUNGAN SOSIAL TERHADAP KECEMASAN DALAM MENYUSUN SKRIPSI PADA MAHASISWA PGSD TINGKAT AKHIR UNIVERSITAS SARI MUTIARA INDONESIA - Sinarsi Meliala; Laksana Tobing; Dwi Nursiti; Krisnatalina Lumbanraja (Psikologi Universitas Sari Mutiara Indonesia, 2021)
The anxiety experienced by students who are compiling their thesis makes students feel depressed due to several factors such as choosing an inappropriate title, the difficulty of finding book references, the limitations of meeting with supervisors due to the PPKM policy by the government. This situation can make students lazy and hinder the process of making the thesis of Psychology Study Program Faculty of Pharmacy and Health Sciences, University of Sari Mutiara Indonesia. The research method used in this research is quantitative research method. finalists who are compiling the Thesis. In this study, the author distributes questionnaires through Google formular with a sample of 50 people. shows the relationship between Social Support Variables on Anxiety in Writing Thesis. The value of R square (R2) is 0.002 which means 0.2% variance of anxiety in writing thesis in PGSD students at the Final Level of Sari Mutiara Indonesia.